Intonation and text in Standard Danish - Grønnum Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1984)
Acoustic analysis of recordings by four Standard Danish speakers shows that each declarative sentence in a text is associated with its own declining intonation contour, but together two or three such contours describe an overall falling slope. Individual sentence intonation contours are steeper and demonstrate greater amounts of resetting between them in a succession of declarative terminal sentences than in a corresponding string of coordinate main clauses. In other words, the closer relation between coordinate structures is reflected in a more coherent or less segregated intonational structure. The results are compared with other languages, and the implications for the abstract representation of Danish intonation are discussed.